HUBUNGAN HUBUNGAN DUKUNGAN SOSIAL ORANG TUA DENGAN RESILIENSI AKADEMIK SISWA KELAS XI DI SMAN 2 TASIKMALAYA: DUKUNGAN SOSIAL ORANG TUA DAN RESILIENSI AKADEMIK - Wulandari, Pebrianti Wulandari (Prodi Bimbingan dan Konseling universitas PGRI Semarang, 2025)
This research aims to determine the relationship between parental sosial support and academic resilience of XIth grade students at SMAN 2 Tasikmalaya. The subjects of this study were 207 people. The research data used two scales, namely parental sosial support and academic resilience scales. Data analysis was carried out using the Pearson product moment correlation method. The technique used for sampling was stratified random sampling. The results of the statistical study showed a correlation (r) of 0.577 with a percentage of 57.7% with ρ 0.005 (ρ <0.005). This shows that there is a positive relationship between parental sosial support and academic resilience. This means that the higher the parental sosial support received, the higher the academic resilience. Conversely, the lower the parental sosial support received, the lower the academic resilience